Unravelling the menace: detection of antimicrobial resistance in aquaculture - P.G. Preena; T. Raja Swaminathan; V.J. Rejish Kumar; I.S. Bright Singh (The Society for Applied Microbiology, 2025)
One of the major problems to be addressed in aquaculture is the prominence of antimicrobial resistance (AMR). The occurrence of bacterial infections in cultured fishes promotes the continuous use of antibiotics in aquaculture, which results in the selection of proliferated antibiotic-resistant bacteria and increases the possibility of transfer to the whole environment through horizontal gene transfer. Hence, the accurate cultivation-dependent and cultivation-independent detection methods are very much crucial for the immediate and proper management of this menace. Antimicrobial resistance determinants carrying mobile genetic transfer elements such as transposons, plasmids, integrons and gene cassettes need to be specifically analysed through molecular detection techniques. The susceptibility of microbes to antibiotics should be tested at regular intervals along with various biochemical assays and conjugation studies so as to determine the extent of spread of AMR. Advanced omic-based and bioinformatic tools can also be incorporated for understanding of genetic diversity. The present review focuses on different detection methods to unearth the complexity of AMR in aquaculture. This monitoring helps the authorities to curb the use of antibiotics, commencement of appropriate management measures and adequate substitute strategies in aquaculture. The long battle of AMR could be overcome by the sincere implementation of One Health approach.